AN EXPERIMENTAL STUDY OF THE STABILITY OF COPPER CHLORIDE COMPLEXES IN WATER VAPOR AT ELEVATED TEMPERATURES AND PRESSURES - Archibald S.M.; Migdisov A.A.; Williams-Jones A.E. (My University, 2002)
The solubility of copper chloride in liquid-undersaturated HCl-bearing water vapor was investigated experimentally at temperatures of 280 to 320°C and pressures up to 103 bars. Results of these experiments show that the solubility of copper in the vapor phase is significant and increases with increasing fH2O, but is retrograde with respect to temperature. This solubility is attributed to the formation of hydrated copper-chloride gas species, interpreted to have a copper-chlorine ratio of 1:1 (e.g., CuCl, Cu3Cl3, etc.) and a hydration number varying from 7.6 at 320°C, to 6.0 at 300°C, and 6.1 at 280°C. Complex formation is proposed to have occurred through the reaction: A1 Log K values determined for this reaction are −21.46 ± 0.05 at 280°C (n = 7.6), −19.03 ± 0.10 at 300°C (n = 6.0), and −19.45 ± 0.12 at 320°C (n = 6.1), if it is assumed that the vapor species is the trimer, Cu3Cl3(H2O)6–8. Calculations based on the above data indicate that at 300°C and HCl fluxes encountered in passively degassing volcanic systems, the vapor phase could transport copper in concentrations as high as 280 ppm. Theoretically, this vapor could form an economic copper deposit (e.g., 50 million tonnes of 0.5% Cu) in as little as ~20,500 yr.